Density‐dependent life history and the dynamics of small populations. (16th July 2013) - Mugabo, Marianne; Perret, Samuel; Legendre, Stéphane; Le Galliard, Jean‐François
Summary: Small population dynamics depend importantly on the strength and shape of density dependence. Unfortunately, the lack of reliable life‐history data often prevents to make accurate demographic predictions for populations regulated by density dependence. We created a gradient from low to high densities in small experimental populations of common lizards ( Zootoca vivipara ) and investigated the shape and strength of the density dependence of life‐history traits during a yearly cycle. We then analysed stochastic population dynamics using one‐sex and two‐sex age‐structured matrix models. Body growth and reproductive performances decreased with density, yearling and adult survival and body size at birth were density‐independent, and juvenile survival increased with density. The density dependence of reproduction was partly explained by positive effects of body size on age at first reproduction and clutch size. Parturition date decreased with density in sparse populations and then increased, providing one of the first empirical evidence of a component Allee effect in the phenology of reproduction. Population growth rate (λ) was most affected by variations in juvenile and yearling survival. However, density at equilibrium was most affected by juvenile access to reproduction and yearling clutch size. Stochastic simulations revealed that negative density dependence buffers the effects of initial density on extinction probability, has positive effects on the persistence of sparse populations and interacts with sex ratio fluctuations to shape extinction dynamics. This study demonstrates that negative density dependence modifies the dynamics of small populations and should be investigated together with Allee effects to predict extinction risks. Abstract : The lack of reliable life‐history data often prevents to make accurate demographic predictions for populations regulated by density dependence. Here, the authors use a realistic field experiment combined with age‐structured population models to investigate the relationship between density, life‐history, population growth and predicted extinction dynamics in the common lizard.